PROBABILITAS LONGSOR TIMBUNAN DI AREA IN PIT DUMP ASAM TIMUR DAERAH KONSESI PT ARUTMIN INDONESIA TAMBANG ASAMASAM, KALIMANTAN SELATAN - Fahrezi, Muhammad Akmal; Zakaria, Zulfiadi; Khoirullah, Nur; Laksana, Prima (Indonesian Mining Journal, 2025)
Open pit mining involves excavation of soil and overburden, which requires a well-planned disposal area to maintain stockpile stability. This is achieved through an analysis of soil bearing capacity and slope stability. The research was conducted at the ASTIM In Pit Dump (IPD) using actual materials. Data were obtained from direct shear tests and physical properties tests, then statistically analyzed to determine the average value, standard deviation, and minimum and maximum relative values. These data were subsquetly input into geotechnical software to perform a slope stability analysis under pessimistic conditions, including water-saturated slopes with a horizontal seismicity coefficient of 0.045. The simulation results did not meet the stability criteria, yielding a safety factor of 0.647. Therefore, engineering design modifications were necessary, including widening the slope angle to 7.61°, consisting of six steps with a level height of 5 meters, a width of 30 meters, and a slope angle of 25°. This redesign resulted in a safety factor (SF) of 1.254 which meets slope stability criteria based on Bowles (1989) and a probability of failure (PoF) of 4.1%, in accordance with the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018.